Creative Thinking and its Role in Industry 5.0 Era - Honzíková, Jarmila; Tomášková, Tetjana (Acta Paedagogica Vilnensia, 2025)
The present study characterizes the emerging era of Industry 5.0 (Gabriel, 2021) and highlights the importance of creative thinking for this future. Industry 5.0 deals with technological development not only through technical and economic evaluation, but also with the help of innovations. It moves the industry’s goals from optimizing production processes to sustainable, socially beneficial and, above all, human-centered production. The technological aspect should be balanced by strengthening human talents and investing in education. The article presents the results of the OECD’s PISA 2022 (OECD, 2024) global survey, which aimed, among other things, to determine the level of creative thinking among 15-year-old respondents from around the world, i.e., the future productive generation. A total of approximately 690,000 pupils, representing around 29 million pupils in 81 countries and economic regions around the world, participated in PISA 2022. The study also shows the teaching strategies that led to achieving the best results in the PISA 2022 tests for pupils from Singapore. In the Czech Republic, 430 schools and nearly 11,000 pupils participated in the survey (PISA 2022 National Report Creative Thinking, 2023). The results of this investigation were contrasted with the results of the Urban Figurative Test of Creative Thinking for primary school pupils in the Czech Republic. The results of this test, however, showed that fifth-grade pupils achieved the highest scores, which has also been proven by other research (Chalupa, 2012; Novotný, 2012). The study also points out social development and its influence on education, where creative thinking will be very important. Based on the results of various studies, this study also presents the competencies necessary in the Industry 5.0 era (Earp, 2024).